Implementasi Pemahaman Keutamaan Menuntut Ilmu Sebagai Penggerak Motivasi Belajar Siswa Ditinjau Dari Hadits Rasulullah SAW - darissalami, Saela; Nur Faizah, Faradina; Alvin Hardyansyah, Muhammad; Siti Nurjanah, Eli (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
This research aims to increase students' learning motivation through understanding the hadith on the priority of seeking knowledge and being able to implement it in learning activities. Currently, many students have low motivation to learn, which makes them reluctant or lazy to study and do not know the purpose or nature of learning. Researchers are trying to explore several hadiths of the Prophet regarding the virtues of seeking knowledge and correlate this with students' learning motivation. The research method was carried out through library research methods. The data collection technique was taken from several articles, studies of Islamic books, and journals. Using content analysis by analyzing the content and exploring themes related to the importance of knowledge and motivation. The results show that in the hadith there is a priority in seeking knowledge, it shows that understanding it can increase students' learning motivation because there is a picture of the glory that will be obtained when they have a high enthusiasm for seeking knowledge. With this research, it is hoped that students can implement these hadiths in learning activities and increase their motivation to learn after understanding the advantages they will find in several hadiths by cultivating critical thinking, daring to ask questions and having high aspirations.